Trends and Predictive Factors of Teacher Digital Literacy: A Literature Review (2020–2025) - Ridwan Abdullah; Neti Karnati; Mohammad Sofwan Effendi; Kamaludin Kamaludin (Journal of Educational Sciences, 2026)
Digital technological developments have reshaped global education, requiring schools to adapt through learning innovation, visionary leadership, and organizational cultures that support digital transformation. School culture plays a crucial role in shaping teachers’ values, behaviors, and attitudes toward effective technology use in the classroom. Teacher digital literacy is a key competency for 21st-century learning and is strongly influenced by collaborative and adaptive school cultures. This study aims to identify, review, and synthesize recent research on the relationship between school culture support and teacher digital literacy in digital school organizations. A Systematic Literature Review (SLR) was conducted using the PRISMA method, analyzing publications indexed in Scopus and Google Scholar from 2000 to 2025. The initial search identified 235 articles, and 22 studies met the inclusion criteria after screening and duplicate removal. Bibliometric analysis using VOSviewer identified four main clusters: teacher competence and basic education, school management and culture, school support and teacher innovation, and digital leadership. The findings indicate that school culture acts as a central link connecting digital leadership, teacher competence, and organizational support in fostering teacher digital literacy. A collaborative, innovative, and visionary school culture is a critical factor in successful technology integration and educational digital transformation.